Mapping the stability of spatial production in integrated crop and pasture systems: Towards zonal management that accounts for both yield and livestock-landscape interactions - McEntee, P.; Bennett, Sarita; Belford, R.; Harper, J.; Trotter, M. (2017)
Precision farming technologies are now widely applied within Australian cropping systems. However, the use of spatial monitoring technologies to investigate livestock and pasture interactions in mixed farming systems remains largely unexplored. Spatio-temporal patterns of grain yield and pasture biomass production were monitored over a four-year period on two Australian mixed farms, one in the south-west of Western Australia and the other in south-east Australia. A production stability index was calculated for two paddocks on each farm. An example is given here for one paddock from Western Australia. The stability index described here is unique in that it combines spatial and temporal variation across both cropping and pasture phases. Co-efficient of variation in yield was used as the threshold value for determining stability. Production in each stability zone was analysed statistically for consistency and correlation between the cropping and pasture phases. Results indicate that the stability index can be used in mixed farming systems to assist in management decisions and for the paddock described, spatial and temporal variation in production between crop and pasture phases was strongly correlated.